Pengaruh Diskon, Kemudahan Penggunaan, dan User Interface (UI) Terhadap Niat Menggunakan Aplikasi McDonald’s (Studi Kasus di Kota Bengkulu) - Andika, Dhevan Wira; Hayadi, Ilsya (Universitas Islam Kadiri, 2023)
This research aims to analyze the influence of discounts, ease of use, and user interface (UI) on intentions to use the McDonald’s application in Bengkulu City. This research uses a quantitative approach by collecting data through questionnaires distributed to respondents who are users of the McDonald’s application in Bengkulu City. The research variables involve discounts as a promotional factor, ease of use as a technological factor, and user interface (UI) as a user interface factor. Data collection was carried out by distributing questionnaires to 144 respondents. The collected data was analyzed using the regression method to identify the influence of each variable on intention to use the McDonald’s application. This research uses SEM-PLS version 4.0. The research results show that discounts, ease of use, and user interface (UI) have a significant positive effect on the intention to use the McDonald’s application in Bengkulu City. Thus, marketing strategies that focus on providing discounts, increasing ease of use, and improving the user interface (UI) can increase user interest and activeness in utilizing the McDonald’s application.